Gender indeterminacy - Silveira, Ronie Alexsandro Teles da (Revista Hipótese, 2016)
Gender indeterminacy is an effective experience for individuals who come to live in contemporary environments increasingly democratic - in the West. This new experience involves the redefinition of relations between individuals and society, between individuals themselves and between them and their sexuality. The aim of this article is to identify and characterize some of the problems that arise due to the experience of gender indeterminacy.
Keywords: Sexuality; Gender; Indeterminacy; Democracy